A review on the electrochemical reduction of CO2 in fuel cells, metal electrodes and molecular catalysts - Lim, Rern Jern (2014)
In this review article, we report the development and utilisation of fuel cells, metal electrodes in aqueous electrolyte and molecular catalysts in the electrochemical reduction of CO2. Fuel cells are able to function in both electrolyser and fuel cell mode and could potentially reduce CO2 and produce energy at the same time. However, it requires considerably high temperatures for efficient operation. Direct reduction using metal electrodes and molecular catalysts are possible at room temperatures but require an additional applied potential and generally have low current densities. Density functional theory (DFT) studies have been used and have begun to unveil possible mechanisms involved which could lead to improvements and development of more efficient catalysts.